Upper respiratory tract mycobiome alterations in different kinds of pulmonary disease - Xu, Xingye; Ding, Fangping; Hu, Xiangqi; Yang, Fan; Zhang, Ting; Dong, Jie; Xue, Ying; Liu, Tao; Wang, Jing; Jin, Qi (Frontiers in Microbiology, 2023)
The human respiratory tract is considered to be a polymicrobial niche, and an imbalance in the microorganism composition is normally associated with several respiratory diseases. In addition to the well-studied bacteriome, the existence of fungal species in the respiratory tract has drawn increasing attention and has been suggested to have a significant clinical impact. However, the understanding of the respiratory fungal microbiota (mycobiome) in pulmonary diseases is still insufficient. In this study, we investigated the fungal community composition of oropharynx swab (OS) samples from patients with five kinds of pulmonary disease, including interstitial lung disease (ILD), bacterial pneumonia (BP), fungal pneumonia (FP), asthma (AS) and lung cancer (LC), and compared them with healthy controls (HCs). Based on high-throughput sequencing of the amplified fungal internal transcribed spacer (ITS) region, the results showed significant differences in fungal composition and abundance between disease groups and HCs. Malassezia was the most significant genus, which was much more abundant in pulmonary diseases than in the control. In addition, many common taxa were shared among different disease groups, but differences in taxa abundance and specific species in distinct disease groups were also observed. Based on linear discriminant analysis effect size (LefSe), each group had its characteristic species. Furthermore, some species showed a significant correlation with the patient clinical characteristics. Our study deepened our understanding of the respiratory tract mycobiome in some diseases that are less studied and identified the commonalities and differences among different kinds of pulmonary disease. These results would provide the solid basis for further investigation of the association between the mycobiome and pathogenicity of pulmonary diseases.